Комплекс середньовічних поховань біля с. Жовтневе (Покровське) в басейні р. Молочної - Рассамакін, Ю.Я. (Археологія, 2018)
Опубліковано середньовічні поховання, п’ять з яких утворювали компактний ґрунтовий могильник, а два інших, які супроводжувалися кіньми, були оточені ровами. The author is publishing the interesting complex consisting of seven medieval burials, located at the edge of the two barrows of the Bronze Age. Five burials composed the flat burial ground and were placed in an arc at regular intervals. Four of them were oriented to the South, one — to the North-West. There was used a stone mortgaging in two niche graves. Beside the burial ground there were discovered two graves accompanied by complete skeletons of horses directed to the West. Both graves were surrounded by the ditches with passes. Some burials were robbed. The inventory of burials is not numerous — the two rings made of pyrophyllite and one iron ring, the bronze gilded arch of a headdress (so-called “horns”), the fragment of upper part of the vessel of the Ancient Rus type and the hand-made vessel with a handle and a neck in form of spout. Analysis of the grave goods allows to date the complex of burials to the Cumanic time. Автор публикует интересный по составу и местоположению (у основания двух курганов эпохи бронзы) комплекс из семи средневековых погребений, пять из которых представляли грунтовый могильник, размещаясь дугой через равные промежутки. Четыре из них были ориентированы в южном направлении, одно — в северо-западном. В двух случаях использовался камень для закладок подбойных могил. Рядом с могильником были совершены два погребения, сопровождавшиеся полными скелетами лошадей, с западной ориентацией. Оба погребения были окружены рвами с проходами. Некоторые погребения были ограблены. Инвентарь незначительный: два пирофилитовых кольца и одно железное; бронзовая с позолотой дужка от головного убора с так называемыми рогами; фрагмент верхней части сосуда древнерусского облика и лепной сосуд с ручкой и оформленным в виде носика-слива горлом. Анализ этого незначительного инвентаря позволяет датировать этот комплекс погребений половецким временем.